Central Venous Catheter-Related Infectious Complications in Pediatric Surgical Patients: A Single-Center Experience - Haldar, Rudrashish; Mandelia, Ankur; Mishra, Prabhaker; Mishra, Ashwani; Siddiqui, Yousuf (Journal of Pediatric Intensive Care, 2021)
The purpose of this study was to estimate the rate of central venous catheter (CVC) colonization and catheter-related bloodstream infections (CRBSIs) in pediatric surgical patients at our institute and to determine the various risk factors for their occurrence. The electronic medical records of 260 children undergoing surgery with simultaneous CVC insertion were retrospectively reviewed. Data on demographics, primary organ system involved, site of CVC, CVC dwell time, CVC colonization, CRBSI, and organisms isolated on culture were collated, categorized, and analyzed. The rate of CVC colonization and CRBSI was 32.8 per 1,000 catheter days (19.6%) and 17.4 per 1,000 catheter days (10.4%), respectively. Patients with CVC colonization and CRBSI had a significantly higher proportion of patients younger than 1 year of age (p = 0.014). The CVC dwell time was significantly higher in both CVC colonization (7 [5–8] days) and CRBSI (6 [5–9] days) patients (p = 0.005). The frequency of femoral catheterization was significantly higher in patients with CRBSI and CVC colonization (p < 0.001). Coagulase negative staphylococcus was the commonest isolate in CVC infections. Age (adjusted odds ratio [OR] = 0.87; p = 0.009), CVC dwell time (adjusted OR = 1.28; p = 0.003), and femoral CVC (adjusted OR = 9.61; p < 0.001) were independent risk factors for CRBSI. Conclusion: This study reveals important observations regarding the infectious complications of CVC in pediatric surgical patients. The rates of CVC colonization and CRBSI in this study were found to be higher as compared with previously reported rates in Western literature. However, these findings are significant in view of paucity of existing literature in pediatric surgical patients. In our study, higher risk of CRBSI was associated with younger age, increasing CVC dwell time, and femoral venous catheterization. We recommend strict compliance with CVC insertion and maintenance practices and adherence to CVC care bundles to minimize these serious complications.
Keywords: central venous catheter; catheter-related bloodstream infection; pediatric; surgery; children; central line; colonization